Study on N-Amino, Protein and Total Glucose of Etawah Crossbreed Goat and Boer Crossbreed Goat Meat Sauce - Khothibul Umam Al Awwaly; Aris Sri Widati; Vina Rahmadani (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2009)
The aim of this study was to know the difference between Etawah crossbreed goat meat sauce and Boer crossbreed goat meat sauce evaluated on N-amino, protein, and total glucose.The material used in the research were meat sauce from Etawah crossbreed goat and Boer crossbreed goat. The result showed that the different species of goat statistically gave  no significant  effect (P>0.05) on N-amino, protein and total glucose of goat meat sauce. Boer crossbreed meat sauce tend higher than Etawah crossbreed meat sauce. Boer crossbreed meat sauce has characteristic as follows: 1.02± 0.02% on N-amino, 6.33±0.15% on protein, and 12.64±0.22% on total glucose. Etawah crossbreed meat sauce has characteristic as follows: 0.94±0.01% on N-amino, 5.28±0.16% on protein, and 11.56±0.25% on total glucose. The best treatment on meat sauce was using Boer crossbreed meat.   Keywords: Etawah crossbreed goat, Boer crossbreed goat, meat sauce